1994
DOI: 10.1143/jjap.33.3339
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Intermediates in Thermal Chemical Vapor Deposition Process Using Tetraethoxysilane

Abstract: The thermal decomposition process of tetraethoxysilane (TEOS) in the gas phase has been studied using a gas-chromatograph mass spectrometer (GC-MS) connected to an electric furnace. TEOS decomposed over 500°C to give a TEOS dimer and trimer. It has been confirmed that formation of TEOS oligomers occurs in the gas phase. Ethylene, acetaldehyde and ethanol were also detected, which are low-molecular-weight products formed by thermal decomposition of TEOS. Ethylene was the principal product among the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 5 publications
0
16
2
Order By: Relevance
“…the gas chromatography. 11 In this study, however, any polymers were not observed in the range of mass number lower than 400. Figure 6 shows the FTIR spectrum of SiO 2 films prepared on p-type Si wafers.…”
Section: Dissociation In Teos/o 2 Plasmacontrasting
confidence: 60%
“…the gas chromatography. 11 In this study, however, any polymers were not observed in the range of mass number lower than 400. Figure 6 shows the FTIR spectrum of SiO 2 films prepared on p-type Si wafers.…”
Section: Dissociation In Teos/o 2 Plasmacontrasting
confidence: 60%
“…The thermal decomposition of tetraethoxysilane (TEOS) in gas phase has been studied (Desu 1989;Van Der Vis et al 1993;Sataka et al 1994;Sirakami et al 1996) in absence and in presence of O2, water and other reagents as proposed by Van Der Vis et al (1993). The decomposition products have been revealed (Van Der Vis et al 1993;Sataka et al 1994) and the scheme of the processes taking place has been proposed (Sirakami et al 1996;Davazoglou and Vamvakas 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The decomposition products have been revealed (Van Der Vis et al 1993;Sataka et al 1994) and the scheme of the processes taking place has been proposed (Sirakami et al 1996;Davazoglou and Vamvakas 1999). Kamiya et al (1990) studied the decomposition of gels based on triethoxymethylsilane (MtEOS) in different media.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies 13,14,27,28 have examined and reported the chemical reaction kinetics of TEOS/O 3 APCVD. Based on these, we developed an overall reaction model, described in more detail elsewhere.…”
Section: B Formation Rate Of Intermediatesmentioning
confidence: 99%